1997
DOI: 10.1021/jp962534l
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of the AlX3···2H2O (X = F, Cl) and AlF3···3H2O Complexes

Abstract: The structures, binding energies, and harmonic vibrational frequencies of AlX3···2H2O (X = F,Cl) complexes have been explored for the first time at the HF, DFT, and MP2 levels using the 6-31G*, 6-31+G*, and the 6-311G** basis sets. The optimizations were performed without symmetry restrictions or other structural limitations. All complexes investigated were found to be energetically stable, regardless of the computational method used. The calculations showed that the DFT(B3LYP)/6-31+G* method is suitable for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…That might also help explain why the capacity of Al 2 O 3 /Si is lower under constant current comparing with the level of the uncoated one in our case, and eventually it increases close to the uncoated one after a few cycles. One possible mechanism of the AlF 3 /Al 2 O 3 formation is the reaction of PF 5 resulting from the decomposition of LiPF 6 (as shown in Equation 2) with trace water leading to HF which further reacts with Al 2 O 3 and forms AlF 3 ·3H 2 O 27, 28…”
mentioning
confidence: 99%
“…That might also help explain why the capacity of Al 2 O 3 /Si is lower under constant current comparing with the level of the uncoated one in our case, and eventually it increases close to the uncoated one after a few cycles. One possible mechanism of the AlF 3 /Al 2 O 3 formation is the reaction of PF 5 resulting from the decomposition of LiPF 6 (as shown in Equation 2) with trace water leading to HF which further reacts with Al 2 O 3 and forms AlF 3 ·3H 2 O 27, 28…”
mentioning
confidence: 99%
“…Although the relative energies of the AlF 3 ·3H 2 O­( 4 ) and AlF 3 ·3H 2 O­( 5 ) isomers are relatively small (2.8 and 3.2 kcal/mol, respectively), such structures should not be present in considerable amounts at room temperature. Interestingly, the earlier studies reported the stability of only one isomeric structure of AlF 3 ·3H 2 O, which corresponds to the isomer AlF 3 ·3H 2 O­( 4 ) shown in Figure , whereas the kinetic stability of lower energy structure AlF 3 ·3H 2 O­( 1 – 3 ) was not predicted. , Finally, the sixth isomer of AlF 3 ·3H 2 O (labeled AlF 3 ·3H 2 O­( 6 ) in Figure ) we found in the 0–20 kcal/mol energy range, exhibits a completely different structure, mostly due to the presence of the H 3 O fragment. It consists of the quasi tetrahedral AlF 3 OH fragment connected to the H 2 O···H 3 O moiety via the hydrogen bonds.…”
Section: Resultsmentioning
confidence: 60%
“…The structure 2 indicates the presence of only one O → Al dative bond; however, the additional stabilization is provided by the formation of hydrogen bond between the two H 2 O molecules localized on the same site of the AlF 3 pyramid. It should be noted that earlier studies reported only one isomeric structure of AlF 3 ·2H 2 O, which corresponds to the AlF 3 ·2H 2 O­( 2 ) isomer, whereas the existence of the global minimum AlF 3 ·2H 2 O­( 1 ) consisting of a planar AlF 3 fragment forming two dative bonds with water molecules was overlooked . The structure of the third AlF 3 ·2H 2 O isomer (labeled 3 in Figure ) is very different and consists of the H 3 O fragment H-bonded to the remaining AlF 3 OH moiety.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Larger quantities of water (in polyhydrated aluminum fluoride) would also not function for this purpose because of a relatively stable extensive hydrogen bonding at the active sites. [46] XPS studies of Makarowicz et al showed that handling of freshly fluorinated HS-AlF 3 under a protecting Ar atmosphere and in a glovebox exposes the samples to higher humidity levels, so that Lewis sites are probably readily covered with OH or H 2 O surface species. [47] However, the authors argue that these Brønsted acid species should be removed by treatment at higher temperature before HS-AlF 3 reagents can fully develop their Lewis acidity.…”
Section: Discussionmentioning
confidence: 99%